2018
DOI: 10.1021/acsaem.8b00615
|View full text |Cite
|
Sign up to set email alerts
|

Topological Design of Inorganic–Organic Thermoelectric Nanocomposites Based on “Electron–Percolation Phonon–Insulator” Concept

Abstract: Thermoelectric nanocomposites (TENCs) with inorganic nanostructures embedded in an organic matrix have attracted much attention in recent years. There is hardly any theory to guide the design of such TENC although various combinations of inorganic fillers and organic matrices are reported. We recently proposed a concept of "electron−percolation phonon−insulator" to provide a guiding ideology for designing inorganic−organic TENC. In this work, we systematically exemplify this theory by measuring the transport p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Compositing organic–inorganic materials is an effective method to further improve the thermoelectric performance of the polymers, because composite can combine the advantages of the organic materials (e.g., lightweight and flexible) and inorganic materials (e.g., high TE performance). Previous research has shown that carbon nanotubes (CNTs) are capable of improving thermoelectric properties of composites. Wang et al demonstrated that the maximum power factor (PF = S 2 σ ) of PEDOT-Tos-PPP/SWCNT films with 35 wt % SWCNT was 37.8 μW m –1 K –2 at room temperature, and it was 1.7 times as high as that of the PEDOT-Tos-PPP films.…”
Section: Introductionmentioning
confidence: 99%
“…Compositing organic–inorganic materials is an effective method to further improve the thermoelectric performance of the polymers, because composite can combine the advantages of the organic materials (e.g., lightweight and flexible) and inorganic materials (e.g., high TE performance). Previous research has shown that carbon nanotubes (CNTs) are capable of improving thermoelectric properties of composites. Wang et al demonstrated that the maximum power factor (PF = S 2 σ ) of PEDOT-Tos-PPP/SWCNT films with 35 wt % SWCNT was 37.8 μW m –1 K –2 at room temperature, and it was 1.7 times as high as that of the PEDOT-Tos-PPP films.…”
Section: Introductionmentioning
confidence: 99%
“…The connected NWs make a conductive path, leading to the drastic increase of σ due to the so-called percolation effect. For percolation theory, σ is represented with the weight fraction W of fillers and the percolation threshold W c in three-dimensional systems as follows: In eq , σ quadratically increases when W exceeds W c. We fitted the experimental data by eq . The fitted line (dashed line) is shown in Figure b, where fitting parameters W c and σ 0 were 45 wt % and 4640 S cm –1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was very difficult to prepare the thermoelectric film, thus a protocol and simple method of film preparation to improve the PF value of the PEDOT‐PSS are demanded. Recently, remarkable progress has been achieved in hybrid thermoelectric materials by introducing an inorganic compound or inorganic nanomaterial into a PEDOT‐PSS film . Hybridization of PEDOT and Bi 2 Te 3 or Te nanomaterials with high thermoelectric properties to achieve good performance is extremely effective, but the use of tellurium compounds is limited by the toxicity and rarity of tellurium.…”
Section: Figurementioning
confidence: 99%